Conceptualising lifestyle "choices:" A qualitative study of GP attitudes towards patients living with "obesity" in the UK - Tanisha Jemma Rose Spratt; Anisa Hajizadeh; Laura Heath; Maryam Kebbe; Paul Aveyard (Elsevier, 2023)
As a complex condition that often arises due to numerous social, environmental and political factors, "obesity" can be understood by healthcare providers as a health outcome that is directly linked to issues that are outside of individual control. UK GPs who participated in a series of focus groups examining attitudes about the role of individual responsibility in weight loss often demonstrated contradictory beliefs when asked about the relationship between obesity, personal responsibility and their patients' (in)ability to take individual action. Whilst GPs who practised in affluent areas were more likely to draw connections between poverty and high rates of obesity, GPs who practised in disadvantaged areas were more likely to discuss the need for all patients to assume personal responsibility for their health behaviours regardless of their individual circumstances. This article examines how GPs from both groups conceptualised personal responsibility in relation to their patients' weight and socioeconomic circumstances. We conclude by outlining the need for GPs to demonstrate empathy when engaging in weight-loss discussions with patients and offer practical support for patients who seek it that is mindful of their material circumstances.